2019
DOI: 10.1155/2019/9529618
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Study for the Removal of Nitrate from Water Using Local Clay

Abstract: Our research aimed at the removal of nitrate ions through adsorption by local clay. A series of batch experiments were conducted to examine the effects of contact time, adsorbent characteristics, initial concentration of nitrate, pH of the solution, concentration, and granulometry of adsorbent. Adsorption isotherms studies indicated that local clay satisfies Freundlich’s model. The rate of reaction follows pseudo-second-order kinetics. Local clay successfully adsorbs nitrates at pH acid. The adsorption capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 32 publications
1
25
0
2
Order By: Relevance
“…The pH is an important parameter that affects the adsorption process (Battas et al, 2019). Figure 5a shows that the adsorption capacity increases until climax and is followed by a decrease with an increase in pH value for all adsorbents.…”
Section: Effect Of Phmentioning
confidence: 99%
“…The pH is an important parameter that affects the adsorption process (Battas et al, 2019). Figure 5a shows that the adsorption capacity increases until climax and is followed by a decrease with an increase in pH value for all adsorbents.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Therefore, additional water purification methods are needed. Methods based on adsorption can be suitable for this purpose, as they are capable of eliminating both organic and inorganic pollutants from water also outside the growing season (Battas et al, 2019). Adsorption-based water purification methods have been shown to be effective in the treatment of municipal wastewaters and urban and agricultural runoff (Singh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the negative value of ΔG o indicates spontaneity of adsorption (Shin et al 2004;Mayer et al 2016;Monfet et al 2017;Ruzhitskaya & Gogina 2017;Xiao et al 2017;Zhang et al 2017;Liu et al 2018;Meena 2018;Prashantha Kumar et al 2018;Berkessa et al 2019;Kim et al 2019;Bacelo et al 2020). The value of ΔG o , which increases (Deng & Shi 2015;Mor et al 2016;Aljeboree et al 2017;Yang et al 2017;Banu et al 2019;Gaidoumi et al 2019 (Chatterjee & Woo 2009;Rezaei Kalantary et al 2016;Song et al 2016;Liu et al 2019aLiu et al , 2019bZhang et al 2019), indicates that the adsorption process is favorable at low and high temperatures, respectively. A positive ΔH o value shows that the process of adsorption is endothermic (Rajeswari et al 2016;Rezaei Kalantary et al 2016;Song et al 2016).…”
Section: Adsorption Thermodynamicsmentioning
confidence: 98%
“…Clay and zeolite have also been explored as adsorbents due to their high surface area. Zeolites can be used at the primary treatment exit as an alternative to the biological removal process in a cost-effective way (Battas et al 2019). The experiment conducted using natural zeolites and hollow fiber membrane contactors for ammonia removal and recovery showed efficiency greater than 98% (Sancho et al 2017).…”
Section: Precipitationmentioning
confidence: 99%